Mr. & Mrs. Dixon hide a body : a novel - Holdich, Jennifer (Sourcebooks Landmark, 2026)
Daisy Dixon is desperate to escape her controlling husband and crumbling estate. But the night before she leaves, a terrible accident changes everything.Instead of calling for help, Daisy and her husband make a choice that binds them together in the worst possible way.When blame starts shifting and loyalties shatter, Daisy realizes her husband isn't just her partner in crime-he's her competition. But if someone is going to prison, it won't be her.Twisted, darkly funny, and deliciously vicious, this is a high-stakes game of love, betrayal, and revenge-where the most dangerous thing in the house isn't the body.It's the marriage.